There Is No 'Virtual Learning': The Materiality of Digital Education - Lesley Gourlay (Springer, 2021)
The distinction between face-to-face and distant digitally-mediated educational engagement is a complex one, and the two modes are often combined in practice, via 'blended learning' or the use of a VLE to support campus-based teaching. The current Covid-19 pandemic has thrown this distinction into relief, in a context where educationalists have been forced to move to fully distant engagement in a very short timeframe. This paper explores how this predicament has brought to the fore the nature of our engagement with digital knowledge practices and screen-based communication, arguing that the notion of 'virtual learning' is a flawed one. Instead, adopting a sociomaterial perspective, it argues that all aspects of digital engagement are in fact grounded in material and embodied entanglements with devices and other artefacts.